Analisis Spektrum Atomik dalam Penentuan Temperatur Eksitasi, Temperatur Elektronik dan Densitas Elektron Plasma Argon - Nur, Muhammad (BERKALA FISIKA, 2009)
Determination of excitation temperature, electron temperature and density of electron has been done through analysis of the atomic spectrum. Atomic spectrum emitted by the argon plasma with a pressure of 1 MPa. Plasma generated in a corona glow discharge reactor. Excitation temperature (Texc) was obtained by using the Boltzmann distribution and the plasma was assumed to occur in Local Thermodynamic Equilibrium (LTE). Electronic temperature (Te) was obtained by using Saha distribution and taking the ratio between the intensity of the observed spectrum (integrated in the frequency interval) with continuous intensity was observed (not integrated). From the two temperatures, and using the Saha distribution, the density of electron/ion (Ne = Ni) can be determined. Argon plasma which was in LTE condition with a pressure of 1 MPa, Texc = 2877.70 K, Te = 21266.54 K and Ne = Ni = 4.60 x 1021 cm-3 were Â obtained Â  Keyword: Excitation temperature, electron temperature, density of electron, atomic spectrum, corona glow discharge, Boltzmann distribution, Saha distribution, Local Thermodynamic Equilibrium